High Power Density Multi-Mosfet-Based Series Resonant Inverter for Induction Heating Applications - M. Saravanan; A. Ramesh Babu (Institute of Advanced Engineering and Science, 2016)
Induction heating application uses uniquely high frequency series resonant inverter for achieving high conversion efficiency. The proposed work focus on improving the practical constraints in requiring the cooling arrangements necessary for switching devices used in resonant inverter due to higher switching and conduction losses. By introducing high frequency Multi- MOSFET based series resonant inverter for the application of induction heating with the following merits such as minimum switching and conduction losses using low voltage grade of automotive MOSFET’s and higher conversion efficiency with high frequency operation. By adding series combination of low voltage ratedMulti MOSFET switches, temperature variation according to the on-state resistance issues can be avoided by sharing the voltage across the switches depends on number switches connected in the bridge circuit without comprising existing system performance parameter such as THD, power factor, output power. Simulation results also presents to verify that the proposed system achieve higher converter efficiency.